The Relationship Between Resilience Level And Quality Of Life Of The Elderly In Sanden District, Bantul, Yogyakarta - Gyfaya Luthfi Aulya Danty; Tri Laksono; Riska Risty Wardhani (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2026)
The increase in the number of elderly people in Indonesia is a demographic phenomenon that has an impact on various aspects of life, especially physical and psychosocial health. The aging process causes the elderly to be vulnerable to experiencing a decline in physical function, chronic diseases, changes in social roles, and psychological disorders such as anxiety and depression that can reduce the quality of life. The quality of life of the elderly is not only influenced by physical conditions, but also by the ability to adapt to the pressures of life. Resilience as an individual's ability to rise and adapt to stressors is an important factor in maintaining the welfare of the elderly. However, the level of resilience in the elderly is not always optimal and there is still variation in quality of life among the elderly community.However, research that specifically examines the relationship between resilience levels and quality of life in community elders in Yogyakarta is still limited. Objective: This study aims to determine the relationship between the level of resilience to quality of life in the elderly in Sanden District, Bantul, Yogyakarta. Methods: This study is a quantitative study with a cross sectional design. The research sample amounted to 120 elderly people aged ≥60 years. Resilience levels were measured using the Connor-Davidson Resilience Scale (CD- RISC 25), while quality of life was measured using WHOQOL-BREF. Data analysis was carried out using the Spearman correlation test. Results: Data analysis using the Spearman correlation test showed a significant relationship between the level of resilience and quality of life of the elderly with a correlation coefficient value of r = 0.294 and a significance value of p = 0.001 (p < 0.05). A positive relationship, which means that the higher the level of resilience, the better the quality of life of the elderly. Conclusions: There is a significant relationship between resilience levels and quality of life in the elderly. Resilience plays an important psychosocial factor in supporting the quality of life of the elderly